EFEKTIVITAS PELAKSANAAN PERCEPATAN PENURUNAN ANGKA KEMATIAN IBU (AKI) DI INDONESIA - Arif Nurhidajat; Dyah Kusumawati (Jurnal Anggaran dan Keuangan Negara Indonesia (AKURASI), 2018)
Maternal Mortality Rate (MMR) is a sensitive indicator that shows the health quality of a country and gets special attention from the United Nations (UN) so that it is placed as one of the targets in the Millennium Development Goals (MDGs). This study tries to look at the effectiveness of efforts to reduce MMR in Indonesia with a focus on research on the analysis of AKI targeting in Indonesia, the effectiveness of the RAN PPAKI program, and the adequacy of budget allocations for efforts to reduce MMR. Furthermore, by using a qualitative analysis approach that adopts the Miles and Huberman (1984) model, results are obtained that the target targets for decreasing the MMR have been quite realistic even though in the determination there are differences in the calculation methods between national targets and the MDGs. In terms of the program plan and its implementation, it was found that the implementation of the RAN PPAKI program was not optimal and effective due to several factors, including: 1) determining the output and efforts to reduce MMR in the form of top down from the Ministry of Health, which paid little attention to needs and characteristics each region; 2) the synchronization and coordination between the activities of reducing MMR financed from the APBN and APBD are not optimal; 3) cross-sectoral coordination that is still very weak and not optimal; and 4) there has been no in-depth evaluation of the impact or relevance of RAN PPAKI's output / activity and budget on the achievement of the reduction in MMR. In addition, the analysis results related to the variable budget allocation for the reduction of MMR, namely the budget to support the implementation of the 2013-2015 RAN PPAKI has been sufficient but the problem is the lack of flexibility in its use, given the allocation of the budget by the center and regions less able to adjust to the needs based on the characteristics in the area. Keywords: Effectiveness, Maternal Mortality Rate, Reduction JEL Classification: H51, I18 Abstrak Angka Kematian Ibu (AKI) merupakan indikator sensitif yang menunjukan kualitas kesehatan suatu Negara dan mendapat perhatian khusus dari Perserikatan Bangsa Bangsa (PBB) sehingga ditempatkan sebagai salah satu target dalam Tujuan Pembangunan Millennium atau Millenium Development Goals (MDGs). Kajian ini mencoba melihat efektivitas upaya penurunan AKI di Indonesia dengan fokus penelitian pada analisis penetapan target AKI di Indonesia, efektivitas program RAN PPAKI, dan kecukupan alokasi anggaran untuk upaya penurunan AKI. Selanjutnya, dengan menggunakan pendekatan analisis kualitatif yang mengadopsi model Miles dan Huberman (1984), diperoleh hasil bahwa target sasaran penurunan AKI yang ditetapkan sudah cukup realistis meskipun dalam penetapannya terdapat perbedaan metode perhitungan antara target nasional dan MDGs. Dari sisi rencana program dan pelaksanaannya diperoleh hasil telitian bahwa pelaksanaan program RAN PPAKI belum optimal dan efektif yang disebabkan oleh beberapa faktor, antara lain: 1) penentuan output dan aktifitas upaya penurunan AKI lebih bersifat top down dari Kemenkes, di mana kurang memperhatikan kebutuhan dan karakteristik masing-masing daerah; 2) sinkronisasi dan koordinasi antara kegiatan penurunan AKI yang dibiayai dari APBN dan APBD belum optimal; 3) koordinasi lintas sektor yang masih sangat lemah dan belum optimal; dan 4) belum adanya evaluasi mendalam terhadap dampak atau relevansi output/aktivitas dan anggaran RAN PPAKI terhadap capaian penurunan AKI. Di samping itu, juga diperoleh hasil analisis terkait dengan variabel alokasi anggaran untuk penurunan AKI, yaitu anggaran untuk mendukung pelaksanaan RAN PPAKI 2013-2015 telah cukup memadai namun yang menjadi masalah adalah kurang adanya fleksibilitas dalam penggunaannya, mengingat peruntukkan anggaran telah ditetapkan oleh pusat dan daerah kurang dapat menyesuaikan dengan kebutuhan berdasarkan karakteristik yang ada di daerah.